Analysis of Food Demand Patterns of Sindh Province, Pakistan - Khurram SHAHZAD *; Muhammad Nadeem SARWAR ** (Pakistan Journal of Applied Economics, 2018)
The study estimates, compare and analyse the food demand patterns of households in the rural and urban Sindh. Estimates of the study are based on data of Household Integrated Economic Survey (HIES) 2010-11, using Linear Expenditure System (LES). The results show that substantial quantities of milk, eggs, vegetables, salt, sugar, wheat, and pulses are taken by households in both the urban and rural Sindh; whereas formers add vegetable oil and later, fruits to this list. There is a visible difference in the marginal budget share and luxuries, necessities, substitutes and complements for both types of households. The difference in results of both the rural and urban recommends that, separate policies should be chalked out for the two areas.